The Open-Ended Legacy of Ralph Wendell Burhoe - Peters, Karl E. (Zygon, 1998)
Through cultivating my thinking, along with that of many others, Ralph Burhoe taught me to understand myself in relational terms. He helped me to appreciate religious traditions on scientific grounds and to see how religion adapts to changing conditions even as it continues to provide meaning and guidance to the wider culture. He restored my belief in an ever-present sovereign God when God is understood in terms of function and system.